The Challenges of Financial Stewardship among Low-Income in Cameroon: The Case of Upper Ifanga in Dikome Presbytery - Lemnyuy , Bongajum Dora; Chenwi, Neba Roland (Journal of Research in Innovative Teaching and Inclusive Learning, 2025)
This research entitled The Challenges of Financial Stewardship among Low-Income Communities in Cameroon: The Case of Upper Ifanga in Dikome Presbytery investigates the financial behaviors and challenges faced by residents of Upper Ifanga. The purpose of the study was to identify the specific challenges of financial stewardship that people in Upper Ifanga face in managing their finances, with emphasis on limited financial knowledge and restricted access to banking services. Using a descriptive survey design, data was collected through structured questionnaires administered to 75 respondents and analyzed using descriptive statistics. The findings revealed that 65.33% of respondents lacked confidence in financial knowledge, and 66.67% had never received financial education. Moreover, 73.33% did not use a budget, and 62.67% never saved money. Access to financial services was also limited, with 84% having no access to formal financial institutions, mainly due to distance, high transaction costs, and lack of identification documents. Additionally, 78% of respondents experienced unstable income, and cultural and family pressures significantly influenced financial decisions. The study concludes that low financial literacy, poor financial habits, restricted financial access, and unstable income are key challenges to sound financial stewardship in Upper Ifanga. It recommends the implementation of financial education initiatives, expand access to user-friendly financial services and strategies to stabilize income in rural communities.